Effect of Hair Coat Shedding Ability on Uterine Artery Hemodynamics in Angus Cattle. (7th May 2021) - Burnett, Randy H; Contreras-Correa, Zully E; Messman, Riley D; Midkiff, Kirsten A; Lemley, Caleb O; Smith, Trent
Abstract: The objective of this study was to evaluate winter hair coat shedding ability and its association with uterine artery hemodynamics. Fall calving, artificially inseminated purebred Angus females (n = 29) were observed once monthly by two trained technicians for winter hair coat shedding and given a visual hair shedding score of 1 to 5 with 1 indicating 100% shed, 2 = 75%, 3 = 50%, 4 = 25%, and 5 indicating 0% shedding of winter hair coat. Month of first shedding (MFS) was determined once a female reached an average hair shedding score of ≤ 3.5 from March until July of 2019 and 2020. Uterine artery blood flow (ABF) was determined using color Doppler ultrasonography at d 150, 180, 210, and 240 of gestation. Total uterine artery (summation of ipsilateral and contralateral arteries) and ipsilateral uterine ABF, diameter, resistance and pulsatility index (PI) were analyzed using repeated measures of the MIXED procedure of SAS with significance declared at P ≤ 0.05. Fixed effects included MFS, day, year, and the respected interactions with covariates of dam body weight, ambient temperature and order of cows ultrasonography examination considered as a random effect. No significant MFS by day of gestation interaction (P > 0.32) was observed for total or ipsilateral ABF (P > 0.23). A MFS by day of gestation (P < 0.04) interaction was observed for both ipsilateral artery diameter and PI, in which females that shed by May had smaller artery diameter (0.74 vs. 0.85 cm) at day 180 of gestation and greater PI (P < 0.02; 1.48 vs. 1.03) at day 150 of gestation compared to June. Shedding ability had an effect on ipsilateral uterine artery development and pulsatility during gestation, possibly affecting the amount of nutrients distributed to the prenatal fetus and subsequent birth weight of the calf from females that shed by May.